Pengembangan Sistem Informasi Monitoring Program Kerja Berbasis Android pada Fakultas Teknik Universitas Nurul Jadid - Fathorazi Nur Fajri; Kamil Malik; Halimatus Sa'diya (GUYUB: Journal of Community Engagement, 2020)
UNUJA has a faculty where each faculty has a work program. Until now, the Faculties and Work Units still have difficulties in monitoring the report benchmarks in achieving targets when doing work. So that the leadership or the Dean has difficulty in monitoring the results of the completion of the work program. From the existing problems, the researcher took a theme about "Monitoring Information System of Faculty Work Program at Nurul Jadid University, Case Study of the Faculty of Engineering based on Android". The method used by the researcher is the waterfall method. In the process, the steps taken are completed one by one first then proceed to the next stage. The purpose of this study is to produce an android-based work program monitoring application to facilitate the monitoring of work program targets and can be accessed online.